RBM45 competes with HDAC1 for binding to FUS in response to DNA damage. Issue 22 (13th November 2017) - Gong, Juanjuan; Huang, Min; Wang, Fengli; Ma, Xiaolu; Liu, Hongmei; Tu, Yingfeng; Xing, Lingyu; Zhu, Xuefei; Zheng, Hui; Fang, Junjie; Li, Xiaoling; Wang, Qiaochu; et al.
Abstract: DNA damage response (DDR) is essential for genome stability and human health. Recently, several RNA binding proteins (RBPs), including fused-in-sarcoma (FUS), have been found unexpectedly to modulate this process. The role of FUS in DDR is closely linked to the pathogenesis of amyotrophic lateral sclerosis (ALS), a progressive neurodegenerative disease that affects nerve cells in the brain and the spinal cord. Given that RBM45 is also an ALS-associated RBP, we wondered whether RBM45 plays any function during this process. Here, we report that RBM45 can be recruited to laser microirradiation-induced DNA damage sites in a PAR- and FUS-dependent manner, but in a RNA-independent fashion. Depletion of RBM45 leads to abnormal DDR signaling and decreased efficiency in DNA double-stranded break repair. Interestingly, RBM45 is found to compete with histone deacetylase 1 (HDAC1) for binding to FUS, thereby regulating the recruitment of HDAC1 to DNA damage sites. A common familial ALS-associated FUS mutation (FUS-R521C) is revealed to prefer to cooperate with RBM45 than HDAC1. Our findings suggest that RBM45 is a key regulator in FUS-related DDR signaling whose dysfunction may contribute to the pathogenesis of ALS.